(untitled) (Global Journal of Medical Research, 2014)
Anaemia is defined as reduction in circulating haemoglobin mass below the critical level. The normal haemoglobin (Hb) concentration in the body is between 12-14 grams percent. WHO has accepted up to 11gm percent as the normal haemoglobin level in pregnancy. However in India and most of the other developing countries the lower limit is often accepted as 10 gms percent.Anaemia ranges from mild, moderate to severe and the WHO pegs the haemoglobin level for each of these types of anaemia in pregnancy at 10.0 – 10.9g/d1 (mild anaemia) 7 – 9.9g/dl (moderate anemia) and < 7g/dl (severe anaemia) (12).